Preparation method of nanoscale high-conductivity tungsten carbonitride heterojunction film
Patent Information
- Application Number
- CN202311680121.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-12-08
AI Technical Summary
然而钨基氧化物作为一种半导体,它的电子传输能力差,活性位点少,因此也阻碍了高效的HER性能
[0014]采用阳极氧化技术在微观纳米尺度上制备出珊瑚状的稳定三维形貌,通过碳氮化在这些微观结构上实现了不同比例的碳氮化钨异质结。该技术使得材料的电导率提高15倍。此外,该材料在活性位点数量、耐蚀性和稳定性等方面也展现出显著的综合性能提升。本技术还具备广泛的调控空间,具体表现为:在700℃时开始氮化,所得为完全的珊瑚状纳米氮化钨;850℃时为碳化钨和氮化钨的共存温度,也即最佳的碳氮化钨异质结制备温度;而1000℃时碳化结束,为完全的珊瑚状纳米碳化钨。在整个过程中,可以通过调整不同的温度,调控碳氮化钨的比例。以及,在该异质结区域还附有不同程度的位错和畸变。这为在大规模工业生产和各种应用领域的定制化需求中,提供广泛的成分比例调控能力。对于未来材料科学和相关应用领域具有重要意义。
Smart Images

Figure HDA0004595886620000011 
Figure HDA0004595886620000012 
Figure HDA0004595886620000013
Abstract
Description
Technical Field
[0001] A method for preparing nanoscale high-conductivity tungsten carbide heterojunction thin films belongs to the field of nanoporous thin film technology. Background Technology
[0002] Electrocatalysis is the process of converting electrical energy into chemical energy, and it has the potential to solve energy and environmental problems. Tungsten-based compounds are considered ideal electrocatalytic materials due to their unique electronic structure and chemical stability. However, tungsten-based oxides, as semiconductors, have poor electron transport capabilities and few active sites, thus hindering efficient HER performance. Tungsten carbide naturally possesses higher conductivity than tungsten oxide and can be used in high-temperature, high-pressure, and high-current-density applications, but its strong adsorption of H atoms during electrocatalytic HER limits further catalytic reactions. To address this, tungsten carbonitride heterojunctions were prepared on a nanoporous basis to effectively enhance the release of H atoms, while increasing conductivity and active sites in and around the heterojunction at dislocations and distortion regions. Furthermore, the electronic state density of tungsten carbonitride near the Fermi level is close to that of Pt, exhibiting Pt-like behavior during hydrogenolysis. This invention proposes a simple and easy-to-implement method for preparing nanoporous tungsten carbonitride heterojunction films using anodic oxidation combined with high-temperature carbonitration, which is of great significance in the field of nanoporous film technology. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing nanoscale high-conductivity tungsten carbonitride heterojunction films. Based on a coral-like porous matrix, the heterojunction of tungsten carbonitride, and the inherent stability of tungsten, the conductivity is increased by 15 times. Furthermore, the number of active sites, corrosion resistance, and stability are significantly increased after carbonitration. Finally, this nanoscale high-conductivity tungsten carbonitride heterojunction has a polycrystalline structure, a simple preparation principle, and the composition ratio of the carbonitride heterojunction can be changed by controlling different temperatures, providing an excellent support for electrocatalysis.
[0004] To achieve the above objectives, the preparation process of the present invention includes the following steps:
[0005] Step 1: Tungsten plate pretreatment. The tungsten plate is pretreated by polishing it with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it is placed in a mixture of ammonia and hydrogen peroxide, such as a mixed solution with a volume ratio of H2O2:NH3·H2O of 3:1, to remove the oxide layer. After that, it is ultrasonically treated in acetone, ethanol, and deionized water respectively.
[0006] Step 2: Prepare a nanoporous tungsten trioxide film by placing the pretreated tungsten metal plate into a 0.2 mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L -1In a mixed electrolyte system of ammonium fluoride, a nanoporous tungsten trioxide film with uniform pore size was prepared by anodic oxidation technology; the voltage was set to 45V and the time was set to 1h, resulting in an amorphous nanoporous morphology.
[0007] Step 3: Place the sample obtained in Step 2 into a tube furnace for the first heat treatment. The heat treatment atmosphere is air, the heating rate is 2℃ / min, the heat treatment temperature is set to 450℃, and the holding time is set to 3h to obtain a stable morphology of tungsten trioxide with a nanoporous coral-like structure.
[0008] Step 4: Immerse the sample obtained in Step 3 in an ethylene glycol solution containing melamine, wherein the concentration of melamine is 0.5 mol / L, and heat and stir at 80°C for 30 min to increase the adsorption of melamine by the nanoporous tungsten trioxide in the solution.
[0009] Step 5: Place the sample obtained in Step 4 into the center of a tube furnace, introduce Ar gas as a protective gas, set the heating rate to 5℃ / min, set the heat treatment temperature to 700-1000℃ (excluding the endpoint value), and set the holding time to 1-3h. A film containing tungsten carbonitride heterojunction can be obtained on the coral-like nanostructure. Preferably, the holding time is 850℃ for 2h.
[0010] In the further step five, CN produced by the pyrolysis of melamine is used as a carbon and nitrogen source to promote the diffusion of C and N atoms into the tungsten oxide phase and gradually replace O atoms, forming tungsten carbide and tungsten nitride in different proportions at different temperatures.
[0011] The coral-like nanostructure obtained in step five is a three-dimensional coral-like nanostructure with one end open and the other end tightly connected to the substrate. The diameter of the coral strip is about 40-60 nm, the pore size is 50-100 nm, and the membrane thickness is about 400±50 nm. The coral-like structure is tightly connected to the substrate and forms a staggered grid arrangement.
[0012] The tungsten carbide heterojunction obtained in step five is a spliced structure of tungsten carbide and tungsten nitride on a coral-like nanostructure. It includes tungsten carbide regions, tungsten nitride regions, and the splice seam between the two, forming a heterojunction. Different degrees of dislocations and distortions are present in the vicinity of this region (see...). Figure 3 The effect of different temperatures is mainly manifested in the following ways: 700℃ is the starting point of nitriding, resulting in completely coral-like nano-tungsten nitride; 850℃ is the coexistence temperature of tungsten carbide and tungsten nitride, which is also the optimal preparation temperature for tungsten carbonitride heterojunctions; 1000℃ is the complete carbonization temperature, resulting in completely coral-like nano-tungsten carbide; different carbonitriding ratios can be controlled by different temperatures during this process.
[0013] Compared with the prior art, the beneficial effects of the present invention are:
[0014] A stable, coral-like three-dimensional morphology was fabricated at the micro- and nanoscale using anodic oxidation technology. Tungsten carbonitride heterojunctions with varying proportions were then achieved within these microstructures through carbonitriding. This technique increased the material's electrical conductivity by 15 times. Furthermore, the material exhibited significant improvements in overall performance, including the number of active sites, corrosion resistance, and stability. This technology also offers a wide range of controllability: initiating nitriding at 700℃ yields fully coral-like tungsten carbonitride nanostructures; 850℃ represents the coexistence temperature of tungsten carbide and tungsten nitride, the optimal temperature for preparing the tungsten carbonitride heterojunction; and carbonization concludes at 1000℃, resulting in fully coral-like tungsten carbide nanostructures. Throughout the process, the proportion of tungsten carbonitride can be controlled by adjusting the temperature. Additionally, varying degrees of dislocations and distortions are present in the heterojunction region. This provides extensive control over the composition ratio for large-scale industrial production and customized applications, holding significant implications for future materials science and related applications. Attached Figure Description
[0015] Figure 1 Example 2: Surface morphology of untreated nanoporous tungsten trioxide thin films
[0016] Figure 2 Example 2: Surface morphology of high-conductivity tungsten carbide heterojunction thin films
[0017] Figure 3 Microstructure of heterojunction, dislocations and distortions in the high-conductivity tungsten carbonitride heterojunction thin film in Example 2
[0018] Figure 4 Phase analysis of the transformation of oxides into tungsten carbonitride in Example 2
[0019] Figure 5 Phase transformation process during carbonitriding at 700-1000℃ Detailed Implementation
[0020] To better understand and illustrate the present invention, the following embodiments and accompanying drawings are provided for further explanation. The scope of protection claimed by the present invention is not limited to the scope shown in the embodiments.
[0021] Example 1:
[0022] A 50mm*100mm*0.1mm tungsten metal plate was pretreated by polishing with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it was immersed in a mixed solution of H2O2:NH3·H2O = 3:1 for 2 minutes to remove the oxide layer. Afterward, it was ultrasonicated in acetone, ethanol, and deionized water for 10 minutes each. Finally, it was dried and placed in a 0.2mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L-1 In an ammonium fluoride electrolyte system, with a voltage set at 45V and a time set at 1h, an amorphous nanoporous morphology was obtained after anodizing. The obtained sample was then placed in a tube furnace for initial heat treatment under an air atmosphere, with a heating rate of 2℃ / min, a heat treatment temperature of 450℃, and a holding time of 3h. The resulting sample was then immersed in an ethylene glycol solution containing melamine (0.5mol / L) and heated and stirred at 80℃ for 20min. After drying, the sample was placed in the center of a tube furnace, with Ar gas introduced as a protective gas. The heating rate was set at 5℃ / min, the heat treatment temperature was set at 700℃, and the holding time was set at 2h. A high-conductivity tungsten carbonitride heterojunction film was obtained.
[0023] Example 2:
[0024] A 50mm*100mm*0.1mm tungsten metal plate was pretreated by polishing with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it was immersed in a mixed solution of H2O2:NH3·H2O = 3:1 for 2 minutes to remove the oxide layer. Afterward, it was ultrasonicated in acetone, ethanol, and deionized water for 10 minutes each. Finally, it was dried and placed in a 0.2mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L -1 In an ammonium fluoride electrolyte system, with a voltage set at 45V and a time set at 1h, an amorphous nanoporous morphology was obtained after anodizing. The obtained sample was then placed in a tube furnace for initial heat treatment under an air atmosphere, with a heating rate of 2℃ / min, a heat treatment temperature of 450℃, and a holding time of 3h. The resulting sample was then immersed in an ethylene glycol solution containing melamine (0.5mol / L) and heated and stirred at 80℃ for 20min. After drying, the sample was placed in the center of a tube furnace, with Ar gas introduced as a protective gas. The heating rate was set at 5℃ / min, the heat treatment temperature was set at 850℃, and the holding time was set at 2h. This resulted in tungsten carbonitride heterojunctions on a coral-like nanostructure.
[0025] Example 3:
[0026] A 50mm*100mm*0.1mm tungsten metal plate was pretreated by polishing with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it was immersed in a mixed solution of H2O2:NH3·H2O = 3:1 for 2 minutes to remove the oxide layer. Afterward, it was ultrasonicated in acetone, ethanol, and deionized water for 10 minutes each. Finally, it was dried and placed in a 0.2mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L -1In an ammonium fluoride electrolyte system, with a voltage set at 45V and a time set at 1h, an amorphous nanoporous morphology was obtained after anodizing. The obtained sample was then placed in a tube furnace for initial heat treatment under an air atmosphere, a heating rate of 2℃ / min, a heat treatment temperature of 450℃, and a holding time of 3h. The resulting sample was then immersed in an ethylene glycol solution containing melamine (0.5mol / L) and heated and stirred at 80℃ for 20min. After drying, the sample was placed in the center of a tube furnace, with Ar gas introduced as a protective gas. The heating rate was set at 5℃ / min, the heat treatment temperature was set at 1000℃, and the holding time was set at 2h. A high-conductivity tungsten carbonitride heterojunction film was obtained.
[0027] Example 4:
[0028] A 50mm*100mm*0.1mm tungsten metal plate was pretreated by polishing with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it was immersed in a mixed solution of H₂O₂:NH₃·H₂O = 3:1 for 2 minutes to remove the oxide layer. Afterward, it was ultrasonicated in acetone, ethanol, and deionized water for 10 minutes each. Finally, it was dried and placed in a 0.2mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L -1 In an ammonium fluoride electrolyte system, with a voltage set at 45V and a time set at 1h, an amorphous nanoporous morphology was obtained after anodizing. The obtained sample was then placed in a tube furnace for initial heat treatment under an air atmosphere, with a heating rate of 2℃ / min, a heat treatment temperature of 450℃, and a holding time of 3h. The resulting sample was then immersed in an ethylene glycol solution containing melamine (0.5mol / L) and heated and stirred at 80℃ for 20min. After drying, the sample was placed in the center of a tube furnace, with Ar gas introduced as a protective gas. The heating rate was set at 5℃ / min, the heat treatment temperature was set at 850℃, and the holding time was set at 1h. A high-conductivity tungsten carbonitride heterojunction film was obtained.
[0029] Example 5:
[0030] A 50mm*100mm*0.1mm tungsten metal plate was pretreated by polishing with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it was immersed in a mixed solution of H₂O₂:NH₃·H₂O = 3:1 for 2 minutes to remove the oxide layer. Afterward, it was ultrasonicated in acetone, ethanol, and deionized water for 10 minutes each. Finally, it was dried and placed in a 0.2mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L -1In an ammonium fluoride electrolyte system, with a voltage set at 45V and a time set at 1h, an amorphous nanoporous morphology was obtained after anodizing. The obtained sample was then placed in a tube furnace for initial heat treatment under an air atmosphere, with a heating rate of 2℃ / min, a heat treatment temperature of 450℃, and a holding time of 3h. The resulting sample was then immersed in an ethylene glycol solution containing melamine (0.5mol / L) and heated and stirred at 80℃ for 20min. After drying, the sample was placed in the center of a tube furnace, with Ar gas introduced as a protective gas. The heating rate was set at 5℃ / min, the heat treatment temperature was set at 850℃, and the holding time was set at 3h. A high-conductivity tungsten carbonitride heterojunction film was obtained.
[0031] Table 1: Process parameters and carbonitriding data used in different embodiments
[0032] 1 700℃ 2h All nitriding 0nm 5.049E+10 8.9 2 850℃ 2h carbonitriding 10nm 8.552E+10 15.1 3 1000℃ 2h Full carbonization 0nm 5.600E+10 9.9 4 850℃ 1h Tungsten carbide < Tungsten nitride 7nm 6.431E+10 11.3 5 850℃ 3h Tungsten carbide > Tungsten nitride 3nm 6.831E+10 12.0 Tungsten trioxide / / none none 5.670E+09 1
[0033] The conductivity test conditions were as follows: measurements were taken at five locations for each sample: the center (C) and the four corners (A, B, D, E); square probes were used with a spacing of 2.5 mm; R = ρ / d = (π / ln2) * Rav; AT510; when the measured value exceeded the instrument's maximum range, calculations were performed using the maximum range; ambient temperature: 23.6℃; humidity: 35%; reference standard: GB / T31838-2019.
Claims
1. A method for preparing a nanoscale high-conductivity tungsten carbide heterojunction thin film, characterized in that, Includes the following steps: Step 1: Tungsten plate pretreatment. The tungsten plate is pretreated by polishing it with sandpaper of grits 600#, 800#, 1200#, and 1500#. Then, it is placed in a mixture of ammonia and hydrogen peroxide to remove the oxide layer, followed by ultrasonic treatment in acetone, ethanol, and deionized water. Step 2: Prepare a nanoporous tungsten trioxide film by placing the pretreated tungsten metal plate into a 0.2 mol·L⁻¹ solution. -1 Ammonium phosphate and 0.5 mol·L -1 In a mixed electrolyte system of ammonium fluoride, a nanoporous tungsten trioxide film with uniform pore size was prepared by anodic oxidation technology; the voltage was set to 45V and the time was set to 1h, resulting in an amorphous nanoporous morphology. Step 3: Place the sample obtained in Step 2 into a tube furnace for the first heat treatment. The heat treatment atmosphere is air, the heating rate is 2℃ / min, the heat treatment temperature is set to 450℃, and the holding time is set to 3h to obtain a stable morphology of tungsten trioxide with a nanoporous coral-like structure. Step 4: Immerse the sample obtained in Step 3 in an ethylene glycol solution containing melamine, wherein the concentration of melamine is 0.5 mol / L, and heat and stir at 80°C for 30 min to increase the adsorption of melamine by the nanoporous tungsten trioxide in the solution. Step 5: Place the sample obtained in Step 4 into the center of a tube furnace, introduce Ar gas as a protective gas, set the heating rate to 5℃ / min, set the heat treatment temperature to 700-1000℃, and set the holding time to 1-3h to obtain a film containing tungsten carbonitride heterojunction on the coral-like nanostructure. The coral-like nanostructure obtained in step five is open at one end and tightly connected to the substrate at the other end. The diameter of the coral strip is 40-60 nm, the pore size is 50-100 nm, and the membrane thickness is 400±50 nm. The coral-like structure is tightly connected to the substrate and forms a staggered grid arrangement.
2. The method according to claim 1, characterized in that, In step one, the volume ratio of H2O2 to NH3·H2O is 3:
1.
3. The method according to claim 1, characterized in that, In step five, keep warm at 850℃ for 2 hours.
4. The method according to claim 1, characterized in that, The tungsten carbide heterojunction obtained in step five is a spliced structure of tungsten carbide and tungsten nitride on a coral-like nanostructure. It includes tungsten carbide regions, tungsten nitride regions, and the splice seam between the two, forming a heterojunction. Dislocations and distortions are present in the vicinity of this region.
5. The method according to claim 1, characterized in that, Step 5: Using CN produced by melamine pyrolysis as a carbon and nitrogen source, C and N atoms diffuse into the tungsten oxide phase and gradually replace O atoms, forming tungsten carbide and tungsten nitride in different proportions at different temperatures. The higher the temperature, the higher the tungsten carbide content.
6. The method according to claim 5, characterized in that, 700℃ is the starting point for nitriding, and the result at 700℃ is a fully coral-like nano-tungsten nitride; 1000℃ is the complete carbonization temperature, and the result at 1000℃ is a fully coral-like nano-tungsten carbide; different carbonization and nitriding ratios are controlled by different temperatures during the process.
7. A nanoscale high-conductivity tungsten carbide heterojunction thin film prepared according to any one of claims 1-6.
Citation Information
Patent Citations
Carbon-coated tungsten nitride and / or tungsten carbide nanowire composite structure and preparation method thereof
CN113755886A
Preparation method for finely-regulated nano-porous tungsten
CN113774461A